Research of lump dynamics on the (3+1)-dimensional B-type Kadomtsev-Petviashvili-Boussinesq equation - Lei, Zhi-Qiang; Liu, Jian-Guo; Rezazadeh, Hadi; Khater, Mostafa M. A.; İnç, Mustafa (World Scientific Publ Co Pte Ltd, 2021)
In this paper, we discuss the interaction of the rational function, hyperbolic as well as exponential function for the (3+1)-dimensional B-type Kadomtsev-Petviashvili-Boussinesq equation with the aid of Hirota's bilinear approach. We find several families of lump-type solutions. This method is a powerful and advantageous mathematical tool for establishing abundant lump solutions of nonlinear partial differential equations. In order to illustrate their dynamic properties, some figures are plotted with determined parameters.
Keywords: (3+1)-dimensional B-type Kadomtsev-Petviashvili-Boussinesq equation; lump solution; Hirota's bilinear method